Rule 3 are you doing it? - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
Pathman Senathirajah reveals the secret to achieving financial freedom with rule 3. A networker's game plan, Rule 3 is about the three principles of network marketing that made many climb up the ranks and cash in bigger checks
Title from title screen
DVD Format
Keywords: Multilevel marketing; Direct marketing